Effect of Work Environment, Compensation and Competence on Employee Job Satisfaction of the Investment Office and One Stop Integrated Service (DPMPTSP) of Central Java Province - Zahra, Diani -; Setyadi, Dody -; Utami, Hadiahti - (Politeknik Negeri Semarang, 2020)
The purpose of this study is to determine the effect of work environment, compensation, and competence on the employee work satisfaction at Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Provinsi Jawa Tengah. Analysis of the data used in instrumental test are validity and reliability test, method of collection data are questionaire and intreview, classic assumption test, multiple linear regression analysis, and hypothesis testing. There are 50 respondents in this research who the government employees, by using purposive sampling method. The results of the hypothesis indicate that the work environment and compensation are partially had no significant affect on the work satisfaction, while the competence were significantly affect on work satisfaction. The results of the coefficient of determination indicate that work environment, compensation and competence affect work satisfaction as much as 63.5%. While the remaining 34.5% work satisfaction influenced by other factors are not examined in this study.